ANALYSIS OF LIQUIDITY, SOLVABILITY, AND PROFITABILITY RATIOS TO ASSESS THE LEVEL OF FINANCIAL HEALTH AT PT YAKIN SEJAHTERA MANDIRI MUARA ENIM TAHUN 2020–2024 - Yenni Suryono; Dwi Oktarina Aryani; Arya Singgih Prasadana (PT. Radja Intercontinental Publishing, 2026)
The sharp fluctuation in net profit of PT Yakin Sejahtera Mandiri Muara Enim during 2020–2024—from a peak of IDR 5.3 billion in 2021 to only IDR 289 million in 2023—raises questions about the overall financial health of this construction services company. This study aims to analyze that condition through liquidity, solvency, and profitability ratios using a descriptive quantitative method based on secondary data from the company's annual balance sheets and income statements. The results show that the company's liquidity and solvency remained strong and stable throughout the period, with the current ratio consistently above 200% and the debt-to-asset ratio below 40%, indicating sound working capital management and a healthy funding structure. In contrast, profitability ratios fluctuated sharply: Return on Equity surged to 182% in 2021 before plunging to 7.55% in 2023 due to rising operational cost pressure and then recovered to 17.19% in 2024. These findings indicate that strong liquidity and solvency do not automatically guarantee earnings stability, making the operational current ratio a key factor for the sustainability of project-based construction businesses such as PT Yakin Sejahtera Mandiri.